Multimodal control of liquid crystalline mesophases from surfactants with photoswitchable tails. Issue 35 (22nd August 2019) - Houston, Judith E.; Kelly, Elaine A.; Kruteva, Margarita; Chrissopoulou, Kiriaki; Cowieson, Nathan; Evans, Rachel C.
Abstract : Azobenzene surfactants transform into a rich variety of single-component liquid crystalline mesophases through strategic control of molecular design, concentration, temperature and light, paving the way to new photoresponsive materials. Abstract : Non-invasive manipulation of the hierarchical structure of functional materials is a key challenge in the advancement of optoelectronics, energy conversion and storage devices and drug delivery systems. Lyotropic liquids crystals, with their long-range order and a rich array of structures, have long been exploited as soft templates to prepare porous materials. The potential to modify the template structure using an external stimulus such as light could lead to new architectures. Here, using a combination of small-angle X-ray scattering and polarised optical microscopy, we decipher the various structure/self-assembly relationships of neutral surfactants bearing photoswitchable tails, which self-organise into a rich variety of lyotropic liquid crystalline mesophases. Facile, multimodal control of the nanoscale morphology of these single-component systems is achieved through: (i) molecular structure, via careful selection of the alkyl tail/ethylene oxide headgroup lengths; (ii) concentration; (iii) temperature; and (iv) photoisomerisation. The nanoscale architectures range from the weakly concentrated hyperswollen lamellar phases, the more common lyotropic lamellar and hexagonal phases, to pure thermotropic liquid crystals; all of which are accessible at room temperature. Photoisomerisation with UV light leads to the reversible destruction of the liquid crystalline phase, which can be spatially controlled through the use of a mask. This extensive study demonstrates the versatility of neutral photosurfactants and paves the way for new applications, such as photoresponsive templates or drug delivery systems.